Purchase Decisions for Event Packages at Hotel Candi Indah Semarang - Nur Khasanah; Dody Setyadi; Taviyastuti (Research Synergy Foundation, 2025)
This research was motivated by fluctuating event package sales at Hotel Candi Indah Semarang, particularly a significant decline in March 2025, which fell by 58% below the target. Three key factors are examined as potential influences: price sensitivity, brand awareness and perceived quality, along with their impact on the purchasing decision of event packages at Hotel Candi Indah Semarang. Data were collected through a literature review, observation, and a Likert-scale questionnaire administered to 80 participants who had previously utilized the hotel's event package services. Data collection utilized a combination of purposive sampling and incidental sampling. Purposive sampling targeted respondents who had previously booked event packages for a minimum of 30 participants, while incidental sampling allowed access to eligible respondents encountered by chance. IBM SPSS version 26 with multiple linear regression was used to analyze the data. All participants provided informed consent prior to participation, and the study adhered to ethical principles in social research. The results showed that purchase decisions for event packages at Hotel Candi Indah Semarang were significantly influenced by price sensitivity, brand awareness, and perceived quality, both partially and simultaneously. In practice, the study's findings can help Hotel Candi Indah Semarang's management develop more effective marketing strategies, notably for improving event package sales. It specifically helps to build tactics based on price sensitivity, perceived quality, and brand awareness. Theoretically, this study enhances the Expectancy Value Theory by demonstrating that price sensitivity, brand awareness and perceived quality constitute significant factors in purchasing decisions within the hospitality sector.